Stimulus Fading Techniques and Token Economic Techniques to Increase Talk Ability in Selective Mutism Students - Sari, Rizka Puspita; Bulantika, Siti Zahra; Murni, Sri (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2022)
Children with selective mutism generally have difficulty in social communication and communication in class which ultimately affects their academic grades. Therefore, there needs to be an effort to help students who experience selective mutism, especially at school. The purpose of this study was to determine the effectiveness of using stimulus fading techniques and economic tokens in improving speaking skills in students with selective mutism. This study used a single-subject design with the subject of a 7-year-old male student who is in grade 1 of elementary school and has selective mutism. The results of the intervention showed an increase in the number of subjects' speaking ability wherein the baseline condition 1 subject spoke 3 times and at baseline 2 subjects managed to speak 21 times. Based on these results, it can be concluded that the use of stimulus fading techniques and economic tokens can improve the subject's speaking ability, especially in answering the teacher's questions and imitating the teacher's instructions.